Preface to the special issue: International perspectives and interactions in education (Journal of Applied Learning and Teaching, 2019)
Our special issue presents a plethora of perspectives and innovative practices in education contexts from across the world. Authors from Canada, the U.S., South America, Europe and China, argue their case on advancements in educational settings and discuss the value of knowledge. Articles published in this issue include papers presented at the International Conference on Education (EDU2019), organized by the Communication Institute of Greece, 13-16/5/2019, in Athens, Greece.